The relationship between body composition and aerobic energy expenditure during technical performance of kendo - Sancassani, Andrei [UNESP]; Pessoa Filho, Dalton M. [UNESP]; Moreira, Pedro V. S.; Nagamine, Kazuo; Neiva, Cassiano M. [UNESP]; Verardi, Carlos E. L. [UNESP] (Int Scientific Literature, Inc, 2017)
Background and Study Aim: There is no reasonable enough scientific knowledge about the aerobic energy expenditure from practicing kendo techniques. Therefore, this study aim is an aerobic energy expenditure ((E) over dot) during the practice of kendo techniques. We verify the hypothesis that E, metabolic rate (as metabolic equivalent unit, MET) and the rate of carbohydrate oxidation are proportional in magnitude to the amount of regional and whole-body fat-free mass (FFM) of the kendo practitioners. Material & Methods: Ten male participants (29.0 +/- 7.6 years, 82.0 +/- 14.2 kg, 174.4 +/- 7.5 cm) underwent body composition evaluation by dual-energy X-ray absorptiometry (DXA), progressive tests to determine (V) over dotO(2max), and performance of kendo protocol, with 11 warm-up and 31 kendo techniques (waza). During the protocol, gas exchange were measured using K4b(2) (COSMED (R)). Based on (V) over dotO(2) and (V) over dotCO2 data, the (E) over dot was calculated using ((E) over dot = 3.941.(V) over dotO(2) + 1.106.(V) over dotCO(2)) and converted to MET, assuming the constant (= 4.184 kJ.kg(-1).h(-1)). Pearson coefficient (r) tested the correlations between regional and whole-body composition data with the values obtained for (E) over dot during warm-up and waza. A significance level of p <= 0.05 was considered. Results: The peak aerobic rate during warm-up and waza reached 7.5 +/- 1.4 (METs) and 8.0 +/- 1.9 (METs), respectively. The FFM of the trunk, lower and upper limbs correlated with total (E) over dot (76.3 +/- 13.2 kcal) during warm-up, with (r) ranging from 0.72 to 0.92, as well as with total (E) over dot (218.5 +/- 34.8 kcal) for the execution of entire protocol (r = 0.67 to 0.75). Conclusion: The practice of kend (o) over bar_ is classified as vigorous exercise requiring high cost of aerobic energy, which is higher in practitioner with larger regional FFM
Keywords: fat-free mass; kakari-geiko; martial art; metabolic equivalent; oxygen consumption